2007
DOI: 10.1097/01.qmh.0000281056.15177.a2
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Process Control for Hospitals

Abstract: The health care industry is slowly embracing the use of statistical process control (SPC) to monitor and study causes of variation in health care processes. While the statistics and principles underlying the use of SPC are relatively straightforward, there is a need to be cognizant of the perils that await the user who is not well versed in the key concepts of SPC. This article introduces the theory behind SPC methodology, describes successful tactics for educating users, and discusses the challenges associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“… 33 There is a ‘rule of 7’ that is generally applied to demonstrate changes that are unlikely to have occurred by chance. 34 35 The SPC for this project demonstrated that following the norovirus outbreak there are more than 7 points under the mean, 11 points, and therefore it is reasonable to assume that this is unlikely to occur by chance.…”
Section: Resultsmentioning
confidence: 92%
“… 33 There is a ‘rule of 7’ that is generally applied to demonstrate changes that are unlikely to have occurred by chance. 34 35 The SPC for this project demonstrated that following the norovirus outbreak there are more than 7 points under the mean, 11 points, and therefore it is reasonable to assume that this is unlikely to occur by chance.…”
Section: Resultsmentioning
confidence: 92%
“…The introduction of control charts in healthcare is recent, compared with its original application to the manufacturing industry. 2,3,[7][8][9][10]20 Most articles in this review focused on adapting control chart methodology and testing its utility to detect significant variations in surgical care retrospectively. While quality metrics in industry allow direct and easy analyses of production processes, the interpretation of surgical outcomes and particularly patient safety seems less straightforward.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of control charts in healthcare is recent, compared with its original application to the manufacturing industry 2,3,7–10,20 . Most articles in this review focused on adapting control chart methodology and testing its utility to detect significant variations in surgical care retrospectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations